Bird community of upper-montane rupestrian fields in South of Minas Gerais State, Southeastern Brazil - Moura, Aloysio Souza de (2020)
Studies about the birds of rupestrian fields in the south of Minas Gerais State in Southeastern Brazil are incomplete, although this region is ornithologically well studied. This bird community has closely associated ecology with fields and the most endangered species of the Cerrado domain. The objective of this manuscript is to create a list of birds which occur in the rupestrian fields of seven municipalities in the south of Minas Gerais State, and further to analyze the birds’ distribution, the endangered species (and their conservation status), and generate bases for future conservation actions. We evaluated seven cities in the south of Minas Gerais State between 2012 and 2018 by using binoculars and cameras. We found a high richness in relation to other open areas, with the Tyrannidae and Trochilidae families being the most representative. We highlight the endangered species in the Cerrado domain which of these species are closely linked to rupestrian fields. The composition is similar to closer areas, with exception to São Thomé das Letras city because it suffers an influence of mining areas. We suggest creating a wildlife protected area to preserve and conserve a great area of rupestrian fields and consequently the associated biota, especially the bird communities